MODEL PSIKOTERAPI DI KALANGAN MUSLIM BANTEN - Fahrurrozi, Fahrurrozi (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2015)
In the field of mental health nowadays, rhe public find several alternatives to heal the psychiatric disorders. Some decades earlier however, efforts to heal their soul were perhaps more focused on models of healing typical of the region. Now public can find alternative healings that come from different regions and even countries. This phenomenon happens in Serang city, the capital of Banten province. Serang society have been encountered by various soul healing techniques (psychotherapy) based on culture, religion, and science. The healing techniques could  be  the  continuation  of the typical model developed by 1he older generation  and  it  also could be an alien healing model that fit into society. Using descriptive-qualitative approach, the researc her argues  that  there are three models of psychotherapy among Muslims in Serang city, namely: ruqyah therapy,  magic  healing  (hikmah),  and rehabilitation model. In the three models of psychotherapy, I discovered similarities and differences in  rhe  process  of  rh e therapy. In ruqyah models, rhe opproach is based on the major religious texts., the Koran and the  Hadith. The magic healing model is a combination of religious lexrs and loca l influence. The last  is the rehabilitation model which is based on the medical psychological approach.